2014
DOI: 10.1128/jcm.03579-13
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-Variable Enterococcus faecium: In Vivo Emergence of Vancomycin Resistance in a Vancomycin-Susceptible Isolate

Abstract: We report the emergence of vancomycin resistance in a patient colonized with a vanA-containing, vanRS-negative isolate of Enterococcus faecium which was initially vancomycin susceptible. This is a previously undescribed mechanism of drug resistance with diagnostic and therapeutic implications. CASE REPORTA 69-year-old man with a medical history of type II diabetes mellitus, urinary retention, and colon adenocarcinoma with hepatic metastases causing portal hypertension and chronic ascites was admitted to the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 10 publications
(14 reference statements)
0
25
0
Order By: Relevance
“…However, none of the isolates contained the orf1, orf2, vanR, or vanS gene. On the basis of these results, it was confirmed that the patient was infected with the recently discovered VVE isolate (1,2). With respect to the two colonized patients, one of the ICU patients was colonized with a strain identical to the index patient's VVE when PFGE analysis was performed and the other patient was colonized with a strain genetically closely related to the index patient's VVE, thus demonstrating transmission among patients (Fig.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…However, none of the isolates contained the orf1, orf2, vanR, or vanS gene. On the basis of these results, it was confirmed that the patient was infected with the recently discovered VVE isolate (1,2). With respect to the two colonized patients, one of the ICU patients was colonized with a strain identical to the index patient's VVE when PFGE analysis was performed and the other patient was colonized with a strain genetically closely related to the index patient's VVE, thus demonstrating transmission among patients (Fig.…”
mentioning
confidence: 53%
“…However, this may have been due to poor source control, given that the isolate was still susceptible to vancomycin on a repeat blood culture. A patient colonized with this organism was recently described, and it was shown in that case that the isolate became resistant to vancomycin in vivo over time during vancomycin therapy (1). A recent study reported that exposure of VVE strains to vancomycin in vitro leads to the development of vancomycin resistance by the constitutive expression of vanHAXYZ gene clusters (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the clinical utility of vancomycin in these cases remains unknown. However, as described in the accompanying paper (24), a recent observation in a 69-year-old patient colonized with VVE showed that subsequent vancomycin exposure resulted in development of vancomycin resistance, with a MIC of 256 g/ml in vivo. Further research involving both in vitro and in vivo studies with animal models are needed to determine whether vancomycin exposure induces resistance in these strains.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, they have spread globally, and VRE remains an important drug-resistant pathogen in many clinical settings (1). Consequently, VRE colonization in patients is monitored in clinical microbiology laboratories by screening rectal swab specimens on selective chromogenic medium and by PCR detection of vanA/vanB (7).Because VanA-and VanB-type VRE are linked to the presence of the vanHAX genes, we were intrigued by the recent identification of strains of vancomycin-susceptible enterococci (VSE) determined by susceptibility testing from Ontario, Canada, which nevertheless were positive for the vanHAX genes, as assessed by PCR (8,9). A similar phenomenon has been described in which genetic alterations in plasmid pS177 give rise to vanA-positive enterococcal isolates that are susceptible to vancomycin (VSE) …”
mentioning
confidence: 99%